Effect Of Smoking And Obesity On Renal Functions In The Middle-Age Men In Basra City (Journal of Pharmaceutical Negative Results, 2023)
The overweight and obesity were increased all over the world as a serious public health concern. BMI is the most common measure used to determine whether the individual was an overweight or obese. There were a wide range of health complications associated with obesity, such as fatigue, shortness of breath, difficulty sleeping, back and joint pain, diabetes, high levels of serum lipids, cardiovascular disease, and chronic kidney disease. On the other hand, tobacco which contained a lot of chemicals, approximately 100 of them were classified as causes or potential causes of smoking-related diseases such as respiratory diseases, lung cancer, cardiovascular disease etc. The current study was performed on 77 subjects (25 smokers, 22 obese and 20 obese smokers, and 10 healthy control) to investigate the effect of smoking and obesity on renal functions in the in middle-age. The study revealed that both smoking and obesity didn’t affected the level of serum creatinine, uric acid and urea, but both significantly elevated the serum level of sodium, potassium and calcium and significantly increased the prevalence of proteinuria. According to the results we can concluded that both obesity and smoking induced significant electrolyte disturbances, and increased the prevalence of proteinuria which consider as sensitive marker of glomeruli injury.